Predicting thoracic kyphosis morphology and the thoracolumbar inflection point determined by individual lumbar lordosis in asymptomatic adults - Pan, Changyu; Bourghli, Anouar; Li, Yunchao; Li, Lei; Kuang, Lei; Wang, Bing; Sun, Jianmin; Lv, Guohua; Obeid, Ibrahim (European spine journal, 2024)
Purpose The aims of this study were to explore the correlations between thoracic kyphosis (TK) and lumbar lordosis (LL) parameters and to build corresponding linear regressions to predict TK morphology and the thoracolumbar inflection point (IP) determined by individual LL parameters in asymptomatic adults. Methods A total of 280 adult healthy volunteers were recruited, and full-spine X-rays were performed for each subject in a standing posture. The following sagittal parameters were measured: cumulative TK, LL, proximal LL (PLL), the apices of TK (TKA) and LL (LLA), the IP and the distance from the plumb line of the thoracic apex (TAPL) and the lumbar apex (LAPL) to the gravity line. The correlations between TK and LL parameters were analyzed, and the corresponding linear regressions were conducted. Results Extensive variations existed in TK alignment, including angular and morphological parameters. In addition, there were statistical correlations of all cumulative TK angles with LL (r values from − 0.173 to − 0.708) and PLL (r values from − 0.206 to − 0.803), TKA and IP with LLA (r s = 0.359 and 0.582, respectively) and TAPL with LAPL (r s = 0.335). The common predictive formulas employed in ASD surgery could include T10-L1 = − 3.6–0.2*LL (R 2 = 0.201), T4-L1 = 3.4–0.5*LL (R 2 = 0.457), TKA = − 10.3 + 1.1*LLA (R 2 = 0.180) and IP = − 12.7 + 1.6*LLA (R 2 = 0.330). Conclusion There were intimate associations between TK and LL parameters in asymptomatic adults. Moreover, predictive models for thoracic alignment, particularly cumulative TK, based on LL parameters were proposed, which could better delineate anatomical relationships, guide thoracic construction during adult spinal deformity surgery and may help preventing proximal junctional failure.